A LCP composite material and its preparation method and use
Through the composite and hot pressing process of LCP, continuous basalt fiber filaments, aromatic polyester and glass microbeads, LCP composite materials with low dielectric constant and low dielectric loss were prepared, solving the problem of existing LCP materials. The problem of meeting the performance requirements of 5G communication devices has been achieved to optimize material performance and reduce processing difficulty.
Patent Information
- Application Number
- CN202411436213.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The dielectric constant of existing LCP materials is between 3.7 and 4.5, which cannot meet the strict standards of 5G communication devices for lower dielectric constants and lower dielectric losses.
LCP composite materials are prepared by LCP, surface-treated continuous basalt fiber filaments, aromatic polyester and surface-treated glass microbeads. The materials are optimized through the granulation, impregnation and hot pressing process of twin-screw extruder dielectric properties.
The low dielectric constant and low dielectric loss of LCP composite materials are achieved, the mechanical properties are improved, and the characteristics of anti-static, high temperature and low temperature resistance are improved, the anisotropy problem of the material is reduced, and the processing difficulty is reduced.
Smart Images

Figure CN118931223B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation and production of plastic materials, and in particular to an LCP composite material and a preparation method and application thereof. Background Art
[0002] As one of the core technologies of 5G, millimeter wave frequency band communication technology has been widely used in many fields such as communication. It solves the problem of spectrum congestion and scarce spectrum resources in the low frequency band (below 6 GHz), and at the same time it can meet the needs of 5G large-capacity and high-speed communication. With the continuous development and maturity of millimeter wave integrated circuits and radio frequency communication systems, future mobile communications will inevitably be composed of millimeter wave communication technology.
[0003] LCP, or liquid crystal polymer, is an advanced polymer material that exhibits liquid crystal properties in a molten state. With its outstanding high strength, high rigidity, high temperature resistance, excellent electrical insulation properties and excellent molding processability, it shines in the fields of electronics, electrical, optical fiber, automobile manufacturing and even aerospace. When LCP is applied to the field of 5G communications, its dielectric constant becomes a key factor in determining the propagation rate of electrical signals. In short, the lower the dielectric constant of LCP, the faster the propagation speed of electrical signals.
[0004] Although LCP has many advantages and can be used at frequencies below 110 GHz, the dielectric constant of most traditional LCP materials still hovers between 3.7 and 4.5, which cannot meet the stringent standards of 5G communication devices for lower dielectric constants and lower dielectric losses. Therefore, the improvement and innovation of LCP materials has become an important topic in the field of materials science, in order to meet the high standards of material performance required by 5G communication technology. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide an LCP composite material and a preparation method and use thereof, so as to solve the problems in the prior art.
[0006] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.
[0007] The present invention provides an LCP composite material, comprising the following raw material components in percentage by weight:
[0008] LCP 25~35%;
[0009] Continuous basalt fiber filaments after surface treatment 60~73%;
[0010] Aromatic polyester 1~5%;
[0011] Surface treated glass beads 1~3%;
[0012] The aromatic polyester is obtained by polycondensation reaction of hydroquinone with isophthaloyl chloride and / or terephthaloyl chloride.
[0013] For example, the dosage of LCP can be 25~30%, 30~32.4%, and 32.4~35%.
[0014] For example, the dosage of the surface treated continuous basalt fiber filaments can be 60-61.5%, 61.5-70%, 70-72.9%, or 72.9-73%.
[0015] For example, the dosage of aromatic polyester can be 1~2%, 2~3%, 3~3.8%, 3.8~4.0%, and 4.0~5.0%.
[0016] For example, the dosage of surface treated glass beads can be 1~2% or 2~3%.
[0017] Preferably, the melting temperature of the LCP is 280°C to 350°C.
[0018] Preferably, the LCP is a thermotropic liquid crystal polymer.
[0019] More preferably, the LCP is Vectra A 950 from Celanese.
[0020] Preferably, the linear density of the continuous basalt fiber filaments is 1000-4800 tex, such as 1000-1200 tex, 1200-1500 tex, 1500-3000 tex, 3000-4000 tex, 4000-4800 tex.
[0021] Preferably, the elastic modulus of the continuous basalt fiber filament is 79.3-110 GPa, and the tensile strength is 3000-4840 MPa.
[0022] Preferably, the standard median particle size of the glass microspheres is 18-60 μm.
[0023] Preferably, the surface-treated glass microbeads are surface-treated by immersing the glass microbeads in a surface treatment agent solution at 20-40° C. and a pH of 4-5 for 2-3 hours.
[0024] More preferably, the glass microbeads are cleaned and dried with ethanol before immersion.
[0025] Preferably, the surface treatment of the surface-treated continuous basalt fiber filaments is as follows: the continuous basalt fiber filaments are immersed in a surface treatment agent solution at 20-40° C. and a pH of 4-5 for 2-3 hours.
[0026] More preferably, hydrochloric acid or acetic acid is used to adjust the pH of the coupling agent solution.
[0027] More preferably, in the surface treatment agent solution, the concentration of the surface treatment agent is 0.1-0.5%.
[0028] More preferably, the surface treatment agent includes a coupling agent, a compatibilizer and a surface treatment agent.
[0029] More preferably, the usage ratio of the coupling agent, the compatibilizer and the surface treatment agent is (1-4): (5-10): (0.3-1).
[0030] More preferably, the coupling agent is γ-aminopropyltriethoxysilane.
[0031] More preferably, the compatibilizer is maleic anhydride grafted PE wax.
[0032] More preferably, the surface treatment agent is hexadecyltrimethylammonium chloride.
[0033] Preferably, the molar ratio of the hydroquinone, the isophthaloyl chloride and the terephthaloyl chloride is (10-12): (7-8): (3-4).
[0034] Preferably, the reaction system of the polycondensation reaction further includes a phase transfer catalyst, and the phase transfer catalyst is triethylbenzylammonium chloride.
[0035] More preferably, the amount of the phase transfer catalyst used accounts for 1.2-1.5% of the total mass of the hydroquinone, the isophthaloyl chloride and the terephthaloyl chloride.
[0036] Preferably, the reaction system of the polycondensation reaction is a water phase-organic phase two-phase system, the solvent of the water phase is water, and the solvent of the organic phase is a halogenated hydrocarbon, which is dichloromethane.
[0037] More preferably, in the aqueous phase system, the molar concentration of the solute is 0.3-0.7 mol / L.
[0038] More preferably, in the organic phase system, the molar concentration of the solute is 0.2-0.5 mol / L.
[0039] More preferably, the aqueous phase system further includes sodium hydroxide, and the molar ratio of sodium hydroxide to the hydroquinone is (2-3):1.
[0040] Preferably, the reaction temperature of the polycondensation reaction is -10 to 50°C.
[0041] Preferably, the reaction time of the polycondensation reaction is 4 to 5 hours.
[0042] Preferably, the LCP composite material includes one or more of the following features:
[0043] a) tensile strength is 60~100Mpa; b) flexural strength is 110~150Mpa; c) flexural modulus is 3300~5000GPa; d) when the test frequency is 35GHz, the complex dielectric constant is 2.60~2.70, and the loss tangent is 3.0×10 -3 ~3.8×10 -3 .
[0044] For example, when the test frequency is 35 GHz, the complex dielectric constant can be 2.65, 2.66, 2.67, 2.68, 2.70, and the loss tangent can be 3.0×10 -3 , 3.2×10 -3 , 3.69×10 -3 , 3.7×10 -3 , 3.73×10 -3 , 3.8×10 -3 .
[0045] More preferably, the LCP composite material comprises one or more of the following features:
[0046] a) tensile strength is 80~100MPa; b) flexural strength is 125~150MPa; c) flexural modulus is 3300~5000GPa; d) when the test frequency is 35GHz, the complex dielectric constant is 2.60~2.70, and the loss tangent is 3.0×10 -3 ~3.8×10 -3 .
[0047] The present invention also discloses a method for preparing the LCP composite material as described above, comprising the following steps:
[0048] The surface treated glass micro beads, the aromatic polyester and the LCP are uniformly mixed and transported to a twin-screw extruder for extrusion and granulation, the granules are heated and melted, and impregnated on the surface of a plurality of parallel continuous basalt fiber filaments after the surface treatment, and after impregnation and pressing, they are cooled to obtain a unidirectional tape; the unidirectional tape is alternately stacked at 0° and 90°, and then hot-pressed. 0° is the moving direction of the unidirectional tape under the action of traction.
[0049] Preferably, the mixture is cooled to room temperature, which in this application is 20-25°C.
[0050] Preferably, during the impregnation, the continuous basalt fiber filaments are pressed. More preferably, the pressure is 3-4 MPa / cm.
[0051] Preferably, the rotation speed of the twin-screw extruder is 80-120 r / min.
[0052] Preferably, the aspect ratio of the twin-screw extruder is 28-40.
[0053] Preferably, the temperature of the twin-screw extruder zone 1 is 270-275°C, the temperature of the zone 2 is 280-285°C, the temperature of the zone 3 is 285-290°C, the temperature of the zone 4 is 290-310°C, and the temperature of the zone 5 is 310-330°C.
[0054] Preferably, the melt processing temperature is 20-30°C higher than the melting temperature of the LCP.
[0055] Preferably, the pressing pressure is 3-4 MPa / cm.
[0056] Preferably, the impregnation is performed by passing the surface-treated continuous glass fiber filaments through a flow channel of a melt impregnation tank for impregnation, and the flow channel width of the melt impregnation tank is 1-3 mm.
[0057] Preferably, before cooling, an electric field adjustment step is performed, specifically: through a heating channel through which an electric field is applied, the direction of the electric field being perpendicular to the moving direction of the impregnated continuous glass fiber filaments.
[0058] More preferably, the temperature of the heating channel is 140-200°C.
[0059] More preferably, the time of passing through the electric field is 1 to 3 minutes.
[0060] More preferably, the electric field strength is 80-120 V / m, further preferably 100 V / m.
[0061] Preferably, the continuous basalt fiber filaments are unwound, bundled, spread and preheated before impregnation.
[0062] More preferably, the unwinding is to place the fiber roll on an unwinding device to ensure that the continuous fiber filaments can be released smoothly and continuously.
[0063] More preferably, the bundling is a bundle formed by a plurality of fiber filaments being gathered together.
[0064] More preferably, the yarn spreading is to spread the bundled fiber bundle through a yarn spreading device to flatten the fiber bundle, reduce air and impurities between fibers, and facilitate subsequent impregnation.
[0065] More preferably, the preheating treatment is to heat the fiber bundle after the yarn is spread. More preferably, the preheating temperature is 180-200°C.
[0066] Preferably, the number of stacked layers is 5 to 15 layers, such as 5 to 10 layers, or 10 to 15 layers.
[0067] Preferably, the hot pressing pressure is 50-100 MPa and the temperature is 290-330°C.
[0068] The present invention also provides the use of the LCP composite material as described above as a 5G communication equipment material.
[0069] The LCP composite material disclosed in the present invention, as well as its preparation method and use, have the following beneficial effects: the LCP composite material obtained by compounding LCP, continuous basalt fiber filaments, aromatic polyester and glass microbeads has low dielectric constant and low dielectric loss, good mechanical properties, antistatic, high temperature and low temperature resistance, and improves the anisotropy caused by excessive differences in transverse and longitudinal properties during LCP processing, thereby reducing the processing difficulty. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 Shown is a schematic diagram of the preparation process for unidirectional tape.
[0071] Figure 2 Schematic showing unidirectional tape with 0º and 90º layup.
[0072] Figure 3 Schematic diagram of a unidirectional tape passing through an electric field under traction.
[0073] Description of reference numerals:
[0074] Figure 1 In the figure, 1 represents a yarn frame, 2 represents a bundling device, 3 represents a yarn spreading device, 4 represents a melt impregnation tank, and 5 represents a cooling roller. DETAILED DESCRIPTION
[0075] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0076] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.
[0077] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0078] The following examples of this application use the following raw materials:
[0079] The grade of LCP is Vectra A950 (manufacturer: Celanese Corporation), and the melting temperature is 280° C. The melting temperature is measured by DSC.
[0080] Continuous basalt fiber filament, brand BEIHAI, model: BH127, linear density is 1200tex, breaking strength is not less than 0.35 N / tex. The breaking strength is tested by GB / T7690.3-2013, and the linear density is tested by the single-filament linear density test in GB / T 14343-2008.
[0081] The surface treatment agent solution is formed by uniformly dispersing the surface treatment agent in water, and the pH value is adjusted to 4 by using acetic acid.
[0082] The surface treatment agent includes a coupling agent, a compatibilizer and a surface treatment agent in a mass ratio of 3:6:0.5, wherein the coupling agent is γ-aminopropyltriethoxysilane, the compatibilizer is maleic anhydride grafted PE wax, and the surface treatment agent is hexadecyltrimethylammonium chloride.
[0083] Maleic anhydride grafted PE wax, product model: ADDIMER 630R.
[0084] The product model of long-chain alkyl modified silicone oil is: RH-8206A, and the manufacturer is Zhejiang Runhe Silicone New Materials Co., Ltd.
[0085] The standard median particle size of glass microspheres is 55µm, the manufacturer is 3M, and the model is 3M™ Hollow Glass Microspheres S15.
[0086] The process for preparing unidirectional tape in the following examples and comparative examples of the present application is as follows: Figure 1 As shown, the fiber reel is placed on the yarn rack 1 and unwound under the traction of the drawing force, and then a plurality of fiber filaments are gathered together to form a bundle through the bundling device 2, and the bundled fiber bundle is unfolded through the yarn spreading device 3 to flatten the fiber bundle, and then the fiber bundle is impregnated and pressed through the melt impregnation tank 4, and after impregnation, it is cooled by the cooling roller 5 to obtain a unidirectional tape.
[0087] Example 1
[0088] This embodiment provides a specific LCP composite material, including the following raw material components in percentage by weight:
[0089] LCP 25%;
[0090] Continuous basalt fiber filaments after surface treatment 73%;
[0091] Aromatic polyester 1.0%;
[0092] Surface treated glass beads 1.0%.
[0093] The preparation method of LCP composite material is as follows:
[0094] 1. Preparation of aromatic polyester:
[0095] (1) Hydroquinone is dissolved in an aqueous solution of sodium hydroxide at a molar concentration of 0.5 mol / L and a molar ratio of sodium hydroxide to hydroquinone of 2.5:1. Triethylbenzyl ammonium chloride is added to obtain solution A. The amount of triethylbenzyl ammonium chloride added is 1.5% of the total mass of hydroquinone, isophthaloyl chloride and terephthaloyl chloride.
[0096] (2) dissolving isophthaloyl chloride and terephthaloyl chloride in dichloromethane at a molar concentration of 0.25 mol / L to obtain solution B;
[0097] (3) Slowly add solution B to solution A, control the temperature below -10°C, and react at 20°C for 5 hours; the molar ratio of hydroquinone to isophthaloyl chloride and terephthaloyl chloride is 10:7:3;
[0098] (4) After the reaction is completed, the reaction solution is filtered, washed and dried.
[0099] 2. Preparation of LCP composite materials
[0100] (1) Surface treatment of continuous basalt fiber filaments: The continuous basalt fiber filaments were immersed in a surface treatment agent solution at 25°C and pH 4 for 3 h. The concentration of the surface treatment agent solution was 0.1 wt%, and then dried at 110°C for 30 min.
[0101] Surface treatment of glass microbeads: The glass microbeads were immersed in anhydrous ethanol, ultrasonically cleaned, vacuum dried, immersed in a surface treatment agent solution at 25° C. and pH 4 for 2 h, the concentration of the surface treatment agent solution was 0.1 wt %, and then filtered, washed with water and dried.
[0102] (2) unwinding, bundling, unwinding and preheating the surface-treated continuous basalt fiber filaments at a preheating temperature of 180°C;
[0103] (3) After the aromatic polyester, LCP and the surface-treated glass microbeads are uniformly mixed, they are transported to a twin-screw extruder for extrusion and granulation. The temperature of the first zone of the twin-screw extruder is 275°C, the temperature of the second zone is 285°C, the temperature of the third zone is 290°C, the temperature of the fourth zone is 310°C, and the temperature of the fifth zone is 330°C. The aspect ratio of the twin-screw extruder is 35, and the rotation speed is 100r / min. After the granules are heated and melted, they are passed into the flow channel of the melt impregnation tank 4. The flow channel width of the melt impregnation tank 4 is 1mm. The surface-treated continuous glass fiber filaments placed on the screw head are impregnated and pressed through the flow channel of the melt impregnation tank 4. The pressing pressure is 3MPa / cm;
[0104] (4) Under the action of the drawing force, the continuous basalt fiber filament moves through the heating channel for 3 minutes. A flat plate capacitor is arranged on the heating channel. The direction of the electric field is perpendicular to the moving direction of the continuous basalt fiber filament; the electric field strength is 100 V / m.
[0105] (5) After cooling to room temperature, a unidirectional tape is obtained; the unidirectional tape is stacked five times alternately at 0° and 90°, and then hot-pressed at 60 MPa and 310°C.
[0106] Example 2
[0107] This embodiment provides a specific LCP composite material, and the raw material component contents thereof are shown in Table 1.
[0108] The preparation method is the same as that in Example 1.
[0109] Example 3
[0110] This embodiment provides a specific LCP composite material, and the raw material component contents thereof are the same as those in Embodiment 1.
[0111] The preparation method is different from Example 1 only in that no electric field is applied to the heating channel, and the rest of the preparation method is the same as Example 2.
[0112] Example 4
[0113] This embodiment provides a specific LCP composite material, the raw material component content of which is the same as that of Example 1, except that the preparation method of the aromatic polyester is different from that of Example 2, specifically: the reaction raw materials are hydroquinone and isophthaloyl chloride, and the molar ratio thereof is 1:1.
[0114] The rest of the preparation method is the same as that in Example 1.
[0115] Example 5
[0116] This embodiment provides a specific LCP composite material, the raw material component content of which is the same as that of Example 1, except that the preparation method of the aromatic polyester is different from that of Example 2, specifically: the reaction raw materials are hydroquinone and terephthaloyl chloride, and the molar ratio thereof is 1:1.
[0117] The rest of the preparation method is the same as that in Example 1.
[0118] Example 6
[0119] This embodiment provides a specific LCP composite material, the raw material component content of which is the same as that of Example 1, except that the preparation method of the aromatic polyester is different from that of Example 2, specifically: the molar ratio of hydroquinone to isophthaloyl chloride and terephthaloyl chloride is 10:3:7. The rest of the preparation method is the same as that of Example 2.
[0120] Comparative Example 1
[0121] Comparative Example 1 is a comparative example of Example 2. The raw material component contents thereof are shown in Table 1. The only difference from Example 2 is that the continuous basalt fiber filaments and glass microbeads are not treated with a surface treatment agent solution.
[0122] Comparative Examples 2 to 5
[0123] Comparative Examples 2 to 5 are comparative examples of Example 2, and the raw material component contents thereof are shown in Table 1. The preparation method is the same as that of Example 2.
[0124] Table 1
[0125]
[0126] The LCP composite materials prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were tested for thickness, tensile strength, flexural strength, flexural modulus, elongation at break, flame retardancy, complex dielectric constant and loss tangent. The test results are shown in Table 2, and the test methods are shown below.
[0127] 1. Tensile strength: ISO 527-2, test speed 5mm / min;
[0128] 2. Flexural strength: ISO 178:2016, test speed 2mm / min;
[0129] 3. Flexural modulus: using method A in ISO 178:2016, test speed is 2mm / min;
[0130] 4. Flame retardant properties:
[0131] Sample preparation: Prepare samples with dimensions of 125 mm in length, 13.0 mm in width and 1.6 mm in thickness. If the test material has different thicknesses, samples of the minimum and maximum thicknesses need to be provided. If the test results of the two are inconsistent, samples of the intermediate thickness are also required.
[0132] Sample pretreatment: Before testing, the samples should be placed in an environment with a temperature of 23 ± 2℃ and a relative humidity of 50 ± 5% for at least 48 hours, then aged at 70 ± 1℃ for 168 hours, and then cooled at room temperature for at least 4 hours.
[0133] Test apparatus: Using a Bunsen burner as the ignition source, fix the sample vertically and place absorbent cotton under the sample to evaluate whether the molten material drips and ignites the cotton wool.
[0134] Vertical combustion test: Fix the sample vertically, place the Bunsen burner at the center point below the sample, and quickly remove the flame after it contacts the sample for 10 seconds. Record the spontaneous combustion time of the sample. After the spontaneous combustion stops, apply the flame again for 10 seconds and remove it. Record the second spontaneous combustion time and the red glow time after the flame is extinguished.
[0135] Test result recording: The test results need to record the burning duration of each sample, the total burning duration, the burning duration after the second flame application, and the glowing burning time.
[0136] Evaluation criteria: Evaluation is based on factors such as the burning time of the sample, whether there is molten material dripping, and whether the dripping material ignites the absorbent cotton underneath.
[0137] V-0 grade requirements: After the sample has been burned twice for 10 seconds, the flame must be extinguished within 30 seconds and no burning material can drip.
[0138] V-1: After the sample has been burned twice for 10 seconds, the flame shall be extinguished within 60 seconds, but no burning material shall drip and ignite the cotton wool below.
[0139] V-2: In the vertical burning test, after the sample has been burned twice for 10 seconds, the flame is extinguished within 60 seconds, and the burning material is allowed to drip, which can ignite the cotton wool 30 cm below.
[0140] 5. Complex dielectric constant: T / CSTM 00990-2023 "Test method for dielectric constant and dielectric loss tangent in millimeter wave frequency band - Quasi-optical cavity test method", test temperature is 24°C, test frequency is 35 GHz.
[0141] 6. Loss tangent: T / CSTM 00990-2023 "Test method for dielectric constant and dielectric loss tangent in millimeter wave frequency band - Quasi-optical cavity test method", test temperature is 24°C, test frequency is 35GHz.
[0142] Table 2
[0143]
[0144] Since the continuous basalt fiber filaments and glass beads were not surface treated, the composite material prepared in Comparative Example 1 had poor interface compatibility. After hot pressing, the product surface had defects and cracks visible to the naked eye.
[0145] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A LCP composite material comprising the following raw material components in percentage by weight: LCP 25~35%; Continuous basalt fiber filaments after surface treatment 60~73%; Aromatic polyester 1~5%; Surface treated glass beads 1~3%; The aromatic polyester is obtained by polycondensation reaction of hydroquinone with isophthaloyl chloride and / or terephthaloyl chloride; The surface-treated glass microspheres are prepared by the following method: soaking the glass microspheres in a surface treatment agent solution at 20-40° C. and pH 4-5 for 2-3 hours; The surface-treated continuous basalt fiber filaments are prepared by the following method: soaking the continuous basalt fiber filaments in a surface treatment agent solution at 20-40° C. and pH 4-5 for 2-3 hours; The surface treatment agent includes a coupling agent, a compatibilizer and a surfactant; The LCP composite material is obtained by the following method: after uniformly mixing the surface-treated glass microbeads, the aromatic polyester and the LCP, conveying them to a twin-screw extruder for extrusion and granulation, heating and melting the granules, impregnating the surfaces of a plurality of parallel continuous basalt fiber filaments after the surface treatment, impregnating and pressing, and cooling to obtain a unidirectional tape; after alternately stacking the unidirectional tape at 0° and 90°, hot pressing and forming.
2. The LCP composite material according to claim 1, characterized in that: The melting temperature of the LCP is 280°C to 350°C; and / or, the LCP is a thermotropic liquid crystal polymer; And / or, the linear density of the continuous basalt fiber filament is 1000-4800tex; And / or, the elastic modulus of the continuous basalt fiber filament is 79.3~110GPa, and the tensile strength is 3000~4840MPa; And / or, the standard median particle size of the glass microspheres is 18-60 μm.
3. The LCP composite material according to claim 2, characterized in that: The LCP selected was Vectra A 950 from Celanese.
4. The LCP composite material according to claim 1, characterized in that: In the surface treatment agent solution, the concentration of the surface treatment agent is 0.1-0.5%; And / or, the usage ratio of the coupling agent, the compatibilizer and the surfactant is (1-4): (5-10): (0.3-1); And / or, the coupling agent is γ-aminopropyltriethoxysilane; And / or, the compatibilizer is maleic anhydride grafted PE wax; And / or, the surfactant is hexadecyltrimethylammonium chloride.
5. The LCP composite material according to claim 1, characterized in that: The molar ratio of the hydroquinone, the isophthaloyl chloride and the terephthaloyl chloride is (10-12): (7-8): (3-4); And / or, the reaction system of the polycondensation reaction further includes a phase transfer catalyst, and the phase transfer catalyst is triethylbenzylammonium chloride; And / or, the reaction system of the polycondensation reaction is a water phase-organic phase two-phase system, the solvent of the water phase is water, and the solvent of the organic phase is a halogenated hydrocarbon; And / or, the reaction temperature of the polycondensation reaction is -10 to 50°C.
6. The LCP composite material according to claim 1, characterized in that: The LCP composite material includes one or more of the following features: a) tensile strength is 60~100Mpa; b) flexural strength is 110~150Mpa; c) flexural modulus is 3300~5000GPa; d) when the test frequency is 35GHz, the complex dielectric constant is 2.60~2.70, and the loss tangent is 3.0×10 -3 ~3.8×10 -3 .
7. A method for preparing the LCP composite material according to any one of claims 1 to 6, characterized in that: The steps include: The surface-treated glass microbeads, the aromatic polyester and the LCP are uniformly mixed and transported to a twin-screw extruder for extrusion and granulation. The granules are heated and melted, and impregnated on the surfaces of a plurality of parallel continuous basalt fiber filaments after the surface treatment. After impregnation and pressing, the unidirectional tape is obtained by cooling. The unidirectional tape is alternately stacked at 0° and 90°, and then hot-pressed.
8. The preparation method according to claim 7, characterized in that: Includes one or more of the following features: The continuous basalt fiber filaments are also unwound, bundled, spread and preheated before impregnation; Before cooling, an electric field adjustment process is performed, specifically: through a heating channel applying an electric field, the direction of the electric field is perpendicular to the movement direction of the impregnated continuous basalt fiber filaments; The hot pressing pressure is 50~100 MPa and the temperature is 290~330℃; The temperature of the first zone of the twin-screw extruder is 270-275°C, the temperature of the second zone is 280-285°C, the temperature of the third zone is 285-290°C, the temperature of the fourth zone is 290-310°C, and the temperature of the fifth zone is 310-330°C; The speed of the twin-screw extruder is 80-120 r / min; The aspect ratio of the twin-screw extruder is 28-40; The melt processing temperature is 20-30°C higher than the melting temperature of the LCP; The pressing pressure is 3~4MPa / cm; The impregnation is performed by passing the surface-treated continuous basalt fiber filaments through a flow channel of a melt impregnation tank (4) for impregnation, wherein the flow channel width of the melt impregnation tank (4) is 1 to 3 mm; Cool to room temperature; The number of stacked layers is 5 to 15.
9. The preparation method according to claim 8, characterized in that: The temperature of the heating channel is 140-200° C.; and / or the electric field strength is 80-120 V / m; and / or the time of passing through the electric field is 1-3 min.
10. Use of the LCP composite material according to any one of claims 1 to 6 as a 5G communication equipment material.
Citation Information
Patent Citations
Polysulfone composite material as well as preparation method and application thereof
CN114456600A
Low-dielectric electronic material and resin composition for the same
JP2002356544A